2021
DOI: 10.3390/environments9010002
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Flood Defense Strategies: Toward Nature-Based Solutions

Abstract: Flood defense strategies have evolved from hard-engineered systems to nature-based solutions that advocate for sustainability to meet today’s environmental, social, and economic goals. This paper aims to analyze the historical progression and evolutionary trends in flood control strategies that have led to nature-based solutions. An evaluative literature review was conducted to narrate the evolution of nature-based flood management approaches for different flood types, river floods, coastal floods, and stormwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Simultaneously, the area serves as space to retain, treat, and store water, rainwater and runoff while offering recreational, cultural, and environmental opportunities. Design strategies combine Nature based Solutions (NbS) [76][77][78][79][80], Water Sensitive Urban Design (WSUD) [74,[81][82][83] and Alternative (or Nature-based) Flood Defence [81,[84][85][86] to generate bluegreen corridors and urban spaces acting as buffers zones to protect the urban environment and enhance natural water systems. This helps manage runoff, reduce urban heat island effects, and guarantee urban ecological connectivity to foster biodiverse corridors for flora and fauna since major environmental pressures in Newcastle LGA include the fragmentation of fauna habitats with limited integration of these in planning locally [7].…”
Section: City-scale To Precinct-scale Thinking: Corrumbah-carringtonmentioning
confidence: 99%
“…Simultaneously, the area serves as space to retain, treat, and store water, rainwater and runoff while offering recreational, cultural, and environmental opportunities. Design strategies combine Nature based Solutions (NbS) [76][77][78][79][80], Water Sensitive Urban Design (WSUD) [74,[81][82][83] and Alternative (or Nature-based) Flood Defence [81,[84][85][86] to generate bluegreen corridors and urban spaces acting as buffers zones to protect the urban environment and enhance natural water systems. This helps manage runoff, reduce urban heat island effects, and guarantee urban ecological connectivity to foster biodiverse corridors for flora and fauna since major environmental pressures in Newcastle LGA include the fragmentation of fauna habitats with limited integration of these in planning locally [7].…”
Section: City-scale To Precinct-scale Thinking: Corrumbah-carringtonmentioning
confidence: 99%
“…The Netherlands's Room for the River program combines traditional measures with NbS, such as creating floodplains and wetlands to manage flood risk [4,5]. These examples illustrate the importance of integrating NbS into river management strategies, promoting sustainable and resilient systems that benefit humans and the environment [6]. NbS offers several advantages, such as enhancing biodiversity, improving water quality, and mitigating the impacts of floods and droughts [1,7].…”
Section: Introductionmentioning
confidence: 99%
“…Flooding in the UK has increased dramatically since 1884 and is now experiencing the highest frequency recorded costing the economy £1.6 billion in 2015/2016 [7]. Hard engineering for flood defence including drains, sewer systems, and gutters have been commonplace in cities since their inception, as a method of quickly draining rainwater, with the intention of providing enough capacity to prevent pluvial flooding in extreme weather conditions [8]. However, the increasing scale of urbanisation, higher annual rainfall, and climate change have all put pressure onto these systems, requiring more protection and swelling the costs of operating, designing, and maintenance [8].…”
Section: Introductionmentioning
confidence: 99%
“…The past decade has seen various studies investigate the most effective NbS for urban pluvial flood risk management [8,14,18,19]. These studies have quantified both the benefits of various methods of NbS and identified the most effective techniques for a range of situations in the urban environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation